REVIVING THOUGHTS: IN SEARCH OF SUWONDO’S RELEVANCE IN MODERN CONTEXT - Pranata, Hedista Rani; Gunawan, Michelle Faustine (Aksen : Journal of Design and Creative Industry, 2025)
Suwondo Bismo Sutedjo is a name that resonates deeply within the Indonesian architectural community. As an academic, architect, and thought leader, his work from the 1960s to 1990s reflects a strong commitment to both architectural practice and the socio-cultural responsibilities that surround it. His legacy lives on not only through built projects but also through a rich body of writings on architecture, urban planning, and education. In January 2024, a significant portion of Suwondo’s archives—comprising articles, photographs, sketches, and personal notes—was acquired by the Museum of Indonesian Architecture. This acquisition provided an opportunity to revisit his ideas through a contemporary lens. This article explores the relevance of Suwondo’s thoughts today through creative curatorial practices that challenge traditional archival exhibitions. A central aim of the project was to dissolve the conventional distance between archive and audience. Visitors were encouraged to interact directly with reproduced archived—turning passive viewing into active engagement. Through workshops and open-ended interpretation of the exhibition, the curatorial process invited public participation in reactivating Suwondo’s legacy and relevance in modern context. In doing so, it demonstrates how archives can become sites of dialogue, where historical architectural thought resonates within present-day contexts.